The Influence of AQ-8 Packaging Drinking Water in Jambi City - Agesha Marsyaf; Mis Sri Violiyanti Simatupang (Badan Pengelola Usaha (BPU) Universitas Jambi, 2023)
Bottled Drinking Water Industry (AMDK). This is what causes a high level of competition between fellow AMDK industries. In addition to the high level of competition between companies in the AMDK industry, the emergence of refill drinking water depots is certainly a problem for companies, because it will be a big threat to the AMDK market . With the variety of AMDK products that crowd Jambi City , there are more diverse choices of AMDK products that are in demand by the public which will influence purchasing decisions in society both the price and the quality of the product. The purpose of this study is to determine the influence of both factors , namely product quality and price on purchasing decisions partially or simultaneously. The research method used is a descriptive quantitative research method. The type and source of data that primary data and secondary data use. Data collection using the method of questionnaires and documentation. Thecollected ata were then analyzed using multiple linear regression analysis. Overall the results of multiple linear regression analysis and hypothesis testing can be concluded that simultaneously Product Quality and Price have a significant effect on Purchasing Decisions While partially Product Quality has a significant effect on Purchasing Decisions and Price has an effect significant to purchasing decisions